On solitons and invariant solutions of the Magneto-electro-elastic circular rod - Hashemi, Mir Sajjad; İnç, Mustafa; Kilic, Bulent; Akgul, Ali (Taylor & Francis Ltd, 2016)
In this paper, we study themagneto-electro-elastic (MEE) circular rod by the aid of Lie group symmetry method. Corresponding symmetry reductions of MEE and its some invariant solutions using the Nucci's method are completely considered too. Subsequently, the soliton solutions are obtained using the first integral method.
Keywords: Field Vector; Magnetothermodynamic Stress; Transient-Responses; Hollow Cylinder; Perturbation; Symmetries